Assembly of nonstoichiometric molybdenum oxide on Si as p-n junction photocathode for enhanced hydrogen evolution - Yoo, Il Han; Lee, Young Jae; Kalanur, Shankara S.; Seo, Hyungtak (Applied Catalysis B: Environmental, 2020)
We propose the utilization of a compositionally tuned MoOx catalyst on Si photocathode for the enhanced hydrogen production and improved charge separation. The efficient MoOx catalyst stoichiometry on Si photocathode was optimized by controlling the deposition gas environment and the target during RF magnetron sputtering. The optimized MoOx stoichiometry on Si photocathode exhibited one of the highest photocurrent density of ∼-30 mA cm−2 at -0.5 V vs RHE under AM 1.5 G illumination. Importantly, the deposition of MoOx on p-Si photocathode causes a significant cathodic shift in the overpotential, indicating the catalytic effect of MoOx. The valence band edge and electrochemical studies were used to analyze the band edge positions with respect to water redox potentials and the formation of p-n junction system. The results of this work demonstrate the advantage of employing a sulfur-free and oxygen-deficient MoOx catalyst on p-Si in p-n junction configuration for the efficient PEC water splitting process.
Keywords: Band alignments; Electrochemical studies; Enhanced hydrogen productions; Interface charge; MoOx; P-n junction; Photocurrent density; rf-Magnetron sputtering; Band alignment; Interface charge transport; MoOx; p-n junction; Si photocathode